Is external hydrocephalus a possible differential diagnosis when child abuse is suspected? Editorial - Akalan, Nejat (Springer Wien, 2022)
This is a retrospective review of 28 infants collected from two different countries and institutions whom their caregivers had been convicted of “child abuse.” The purpose, descriptions, and the conclusion are well accepted but the article as a whole is rather confusing for the general neurosurgical community. The authors speculate that the terms, “benign enlargement of the subarachnoid spaces (BESS)” and subdural collections are sometimes misdiagnosed leading serious medico-legal problems. Subdural collections represent various conditions which are used interchangeably such as subdural hygroma, chronical subdural hematoma, and external hydrocephaly.
Keywords: External Hydrocephalus; Differential Diagnosis; Child Abuse